Robert Musil: Literature as Experience - Burton Pike (Studies in 20th & 21st Century Literature, 1994)
Trained as a scientist and empirical psychologist, Robert Musil offers an illuminating instance of a post-Nietzschean modernist writer whose endeavor was to develop an experimental literary language that would more adequately represent experience as psychology and philosophy were coming to understand it. Musil's enterprise, based on regarding literature as experience rather than as a formal construct of language only, is not best examined by structurally-based language or discourse analysis and criticism. Like Mach and William James coming along at the end of the idealistic tradition in European thought, Musil wanted to fashion a language that would permit objective communication of the whole complex flow of experience from person to person and within society as a whole, and thus make true communication possible. Musil's fiction grew out of the phenomenological enterprise, but the focus here is on his interest in shaping this philosophical mode of thinking into a precise fictional vehicle—an approach often overlooked in comparing the practice of writers' and philosophers' ideas.
Keywords: Robert Musil; scientist; empirical psychologist; post-Nietzschean; modernist; writer; experimental literary language; langauge; psychology; philosophy; represent experience; literature as experience; structurally-based language; discourse analysis; criticism; Like Mach; William James; idealistic tradition; idealist; objective communication; society; individual; mode of thinking; philosophical mode of thinking